2022
DOI: 10.1108/cbth-09-2021-0216
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transformational, transactional and authentic leadership on innovation: the mediating role of organizational culture

Abstract: Purpose This study aims to investigate the effects of different leadership styles, transformational, transactional and authentic leadership, on travel agents’ innovational behavior, with organizational culture as a mediator. Design/methodology/approach The study aim was achieved by using an integrative model using LISREL 8.80. Quantitative research was used using a questionnaire. A convenient sampling technique was used to select the sample. A total of 500 questionnaires were distributed to travel agents, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Organizational culture can be defined as a collection of fundamental values that are shared by the members of an organization (Zheng et al, 2019). Rashwan and Ghaly (2022) provide a fundamental explanation of organizational culture as the underlying framework of organizations, which is grounded in the values, beliefs, and assumptions upheld by members of the organization. Furthermore, the diverse hues of the keywords in Figure 10 enable us to determine the mean publication year of all publications that encompass these phrases.…”
Section: Document Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational culture can be defined as a collection of fundamental values that are shared by the members of an organization (Zheng et al, 2019). Rashwan and Ghaly (2022) provide a fundamental explanation of organizational culture as the underlying framework of organizations, which is grounded in the values, beliefs, and assumptions upheld by members of the organization. Furthermore, the diverse hues of the keywords in Figure 10 enable us to determine the mean publication year of all publications that encompass these phrases.…”
Section: Document Analysismentioning
confidence: 99%
“…It also inspires and motivates employees to engage in innovative behaviour within an organisation (Alrowwad et al, 2020). Rashwan and Ghaly (2022) found that transformational leadership promotes a secure environment that stimulates innovation among employees. Furthermore transformational leadership refers to a style of leadership characterized by charismatic, visionary, and inspirational behaviors that influence employees to exceed their goals and perform beyond the established expectations in the workplace (Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao (2010) proposed that, when combined with purposeful actions, transactional leadership is likely to evoke positive emotions among employees, thereby driving innovation. Rashwan (2022) defined transactional leadership as a leader-member relationship based on exchanges, where superiors mainly motivate employees through direct rewards or punishments, focusing on employees' organizational contributions. Miao (2020) found that transactional leaders focus on achieving organizational goals, actively identify and correct deviations from standards, excel in emergency management, and emphasize excellence in management.…”
Section: Literature Review Findings (1) Innovation Performance and Tr...mentioning
confidence: 99%
“…The acquisition and dissemination of knowledge are crucial elements of businesses, penetrating many of their aspects, such as organizational culture, communication and employees (Adhikari and Shrestha, 2023; Rashwan and Ghaly, 2022). Overall, the strategic components of knowledge management include the processes of knowledge development, capture, sharing and usage.…”
Section: Literature Reviewmentioning
confidence: 99%